Party Capability versus Court Preference: Why Do the "Haves" Come Out Ahead?—An Empirical Lesson from the Taiwan Supreme Court. (5th February 2014) - Chen, Kong-Pin; Huang, Kuo-Chang; Lin, Chang-Ching
Abstract : Using civil appeals data on Taiwan's Supreme Court (TSC), this article revisits the well-known question of whether the "haves" come out ahead in litigations. We first show that the higher-status litigants indeed mobilized stronger legal representation and obtained more victories than the lower-status litigants. However, we submit that that the party capability theory cannot fully explain the advantages the "haves" enjoyed over the "have-nots." Further analysis reveals that the TSC's exercise of discretionary jurisdiction also played an important role by strongly favoring the governmental litigants at the agenda-setting stage. We argue that the TSC's preference in this regard was induced by the TSC judges' self-identification as part of government. In conclusion, our empirical investigation shows that both party capability and court preference contribute to influence the outcomes of appeals. ( JEL K4)